Penerapan Problem Solving Untuk Meningkatkan Motivasi dan Hasil Belajar IPS - Sihole, Beresman (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The problem in this research is that teachers are not optimal in applying various learning methods. Learning is still one-way so learning seems boring. In addition, students are less enthusiastic in asking questions, ideas, and opinions during learning. This classroom action research was carried out at SMPN 4 Simanindo with the research subjects being 23 students of class IX-C. The use of problem solving methods in Social Science learning material Modernization and Socio-Cultural Change can increase student motivation. This is indicated by the increase in learning motivation showing an increase from 11 students or 47.83% in the initial study to 21 students or 91.30% in the last cycle. After the improvement of student learning completeness was carried out by 91.30%. It can be concluded that the use of problem solving methods for learning Social Sciences material on the location and area of Indonesia can improve student learning outcomes. Keywords: modernization; problem solving; socio-cultural Abstrak: Permasalahan dalam penelitian ini adalah guru belum optimal dalam menerapkan metode pembelajaran yang bervariasi. Pembelajaran masih bersifat satu arah sehingga pembelajaran terkesan membosankan. Selain itu, peserta didik kurang antusias dalam mengemukakan pertanyaan, gagasan, dan pendapat saat pembelajaran. Penelitian tindakan kelas ini dilaksanakan di SMPN 4 Simanindo dengan subjek penelitian adalah peserta didik kelas IX-C yang berjumlah 23 orang. Penggunaan metode problem solving pembelajaran Ilmu Pengetahuan Sosial materi Modernisasi dan Perubahan Sosial Budaya dapat meningkatkan motivasi siswa. Hal ini terindikasi dari peningkatan motivasi belajar menunjukkan peningkatan dari 11 peserta didik atau 47,83% pada studi awal menjadi 21 peserta didik atau 91,30% pada siklus terakhir. Setelah dilaksanakan perbaikan ketuntasan belajar siswa sebesar 91,30%. Dapat disimpulkan penggunaan metode problem solving pembelajaran Ilmu Pengetahuan Sosial materi letak dan luas Indonesia dapat meningkatkan hasil belajar siswa. Kata Kunci: modernisasi; problem solving; sosial budaya